EXPLORING ABBREVIATED RAILWAY TERMINOLOGY IN ENGLISH: A COMPREHENSIVE ANALYSIS - Kubanova, Ilmira (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study investigates the provision and usage of abbreviated terms within railway terminology in the English language. Through a thorough examination of existing literature, an analysis of linguistic features, and a survey of railway industry professionals, this research aims to uncover prevalent abbreviated terms, their formation, and their significance within the railway domain. By shedding light on the use of abbreviations in railway terminology, this study contributes to a deeper understanding of communication practices within the industry.